PENGARUH MANAJEMEN MODAL KERJA DAN PERPUTARAN KAS TERHADAP PROFITABILITAS PADA PERUSAHAAN WISMILAK INTI MAKMUR TBK DI BURSA EFEK INDONESIA - Kusuma, Arya Wijaya; Choerudin, Achmad; Darmaningrum, Kurniawati (Gapenas Publisher, 2025)
This study aims to determine the effect of working capital management and cash turnover on profitability at Wismilak Inti Makmur Tbk. This study is a quantitative study using multiple linear regression analysis. The population in this study is the entire financial statements of PT Wismilak Inti Makmur Tbk in the year (2017–2023). The sample in this report is the income statement of the year (2017-2023). The data collection technique used is the library research method, namely research used by the author through book literature to support relevant theoretical foundations in compiling a thesis, and the internet research method (Online Research), namely, using the internet media as a search for information in the form of theories, as well as supporting data for the research to be carried out. The results of this study indicate that working capital has a significant positive effect on profitability and cash turnover doesn't have a significant effect on profitability at PT Wismilak Inti Makmur Tbk